2018
DOI: 10.4183/aeb.2018.36
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipoprotein-Associated Phospholipase A2 in Males With Metabolic Syndrome and Obstructive Sleep Apnea

Abstract: Context. Lipoprotein-associated phospholipase A2 (Lp-PLA2) is a novel biomarker for cardiovascular diseases (CVD) risk estimation with high specificity for vascular inflammation. Few studies have investigated Lp-PLA2 levels in patients with metabolic syndrome (MetS) and obstructive sleep apnea syndrome (OSAS).Objective. This study aimed to evaluate the role of Lp-PLA2 levels as a marker of vascular inflammation that contributes to cardiometabolic dysfunction in patients with MetS and OSAS.Design. This is a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In agreement with a pronounced phospholipase activity of EL and a high affinity of EL for HDL phospholipids [9,[15][16][17]46,47], we observed a negative correlation between EL and HDL phospholipid content (HDL-PL/HDL-apoA-I) in HV, but not in MS patients (Figure 4B). It is conceivable that in MS, despite higher EL serum levels compared to HV (Table 2), the decreased activity of lipoprotein lipase, an enzyme involved in the biogenesis of HDL [48], as well as the degradation of HDL phospholipids by upregulated other serum phospholipases [49,50], or adiposity, known to affect HDL size, composition, and subclass distribution [51], mask the impact of EL on the phospholipid content of HDL.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with a pronounced phospholipase activity of EL and a high affinity of EL for HDL phospholipids [9,[15][16][17]46,47], we observed a negative correlation between EL and HDL phospholipid content (HDL-PL/HDL-apoA-I) in HV, but not in MS patients (Figure 4B). It is conceivable that in MS, despite higher EL serum levels compared to HV (Table 2), the decreased activity of lipoprotein lipase, an enzyme involved in the biogenesis of HDL [48], as well as the degradation of HDL phospholipids by upregulated other serum phospholipases [49,50], or adiposity, known to affect HDL size, composition, and subclass distribution [51], mask the impact of EL on the phospholipid content of HDL.…”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies have investigated the roles of Lp-PLA2 in OSAS. In a previous study, Moise et al found that serum Lp-PLA2 levels were higher in OSAS patients with metabolic syndrome than those without [16]. Besides, Barcelo et al evaluated the antioxidant capacity in male patients with OSAS, which demonstrated decrease of total antioxidant capacity and increase of Lp-PLA2 values among these patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…To date, a few studies have investigated the roles of Lp-PLA2 in OSAS patients [14][15][16]. However, little is known about the association between Lp-PLA2 and CVD occurrence in OSAS patients.…”
Section: Introductionmentioning
confidence: 99%
“…The question arises as to how the complex pathophysiological constellation in MS drives associations of EL with the serum levels and lipid content of apoB-containing lipoproteins. One can speculate that in MS the upregulated EL, decreased LPL, and elevated TG-rich VLDL and sdLDL, together with an inflammatory environment and deregulated endogenous EL inhibitors as well as other altered serum lipases and lipid transfer proteins, facilitate these associations of EL with apoB-containing lipoproteins [ 29 , 30 , 31 , 32 , 33 , 34 ]. Importantly, serum levels of EL do not obligatorily reflect its enzymatic activity, and the associations of EL with apoB-containing lipoproteins in previous studies were observed by comparing experimental groups that strikingly differed in the bioavailability of the enzymatically active EL: humans with genetically inactive EL vs. those with normal EL activity, humans and mice with derepressed EL due to ANGPTL3 inactivation vs. those with physiological EL activity, or mice with hepatic EL overexpression vs. mice with physiological EL expression [ 18 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%